Efficacy of combination therapy of mid‐urethral sling and low‐dose Abobotulinumtoxin‐A injection in mixed urinary incontinence. Issue 1 (16th September 2021) - Hajebrahimi, Sakineh; Shamsi‐sisi, Hooshang; Jahantabi, Elham; Salehi‐Pourmehr, Hanieh; Hashim, Hashim
Abstract: Objectives: To determine the outcome of combined transobturator tape sling (TOT) and low dose intradetrusor injection of Abobotulinumtoxin‐A (Abobot‐A, Dysport®) in women with mixed urinary incontinence (MUI). Methods: This randomized, active comparator‐controlled, parallel‐group, two‐part clinical trial was conducted on women who had positive Valsalva leak point pressure (VLPP) + detrusor overactivity (DO), cough‐associated DO. In Part 1, 20 women with MUI who had a failure of medical and behavioral therapies to cure MUI, randomized in two groups receiving TOT surgery alone, or in combination with Dysport® injection ( n = 10 in each group), and then Part 2 was initiated as a prospective open‐label on 40 more patients. We performed cystoscopy and injected 300 U of Dysport®in 20–30 intradetrusor injection sites in each patient. Results: The patient's symptoms in both groups decreased significantly after treatment. The symptoms were improved significantly in the combination therapy group according to the International Consultation on Incontinence Questionnaire‐overactive bladder (ICIQ‐OAB) questionnaire ( p < .001), and International Consultation on Incontinence Questionnaire‐urinary Incontinence‐short form (ICIQ‐UI‐SF) ( p = .041) in comparing with the TOT group. In Part 2, the mean score was 17.10 (4.75) for ICIQ‐UI‐SF and 9.22 (2.89) for ICIQ‐OAB before the treatment. Twelve weeks after the intervention, the median (interquartile range: IQR) of ICIQ‐OAB symptoms (2.0 [3.0]; p < .001) and ICIQ‐UI‐SF decreased, too (1. 0 [2.0]; p < .001). Considering improvement using Patient Global Impression of Improvement scale, 46 (92.0%) stated that they had significant subjective improvement of their symptoms. Conclusions: Combination therapy was accompanied with a promising effect in the patients with MUI according to the results of standardized questionnaires. However, further studies with controlled arms are recommended.